Level of Sedentary Behavior and Its Associated Factors among Saudi Women Working in Office-Based Jobs in Saudi Arabia - Albawardi, Nada M. (Int J Environ Res Public Health, 2017)
Research in Saudi Arabia has revealed a shocking level of insufficiently physically active adults, particularly women. The risk of sedentary behavior will likely increase as the number of women with office-based jobs increases. The aim of this study is to determine the level of sedentary behavior, and its associated factors, among Saudi women working office-based jobs in the city of Riyadh. A cross-sectional study of 420 Saudi female employees at 8 office-based worksites were measured to determine body mass index and were given a self-administered survey to evaluate their level of physical activity and sedentary behavior. Median sitting time on work days was 690 min per day (interquartile range, IQR 541–870), with nearly half accumulated during work hours, and 575 min per day (IQR 360–780) on non-work days. Predictors of work day sitting time were level of education, number of children, and working in the private sector. Number of children, whether they were single, and whether they lived in a small home were found to predict non-work day sitting time. This study identifies Saudi women in office-based jobs as a high-risk group for sedentary behavior. There is a need to promote physical activity at worksites and reduce prolonged sitting.